Analisis Kebijakan Harga Terhadap Risiko Bisnis Dan Perkembangan Produk Asuransi Syariah - Ely Aswita (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2019)
The purpose of this study is to find out how the price calculation is used to determined contributions, what factors that can influenced Sharia insurance premiums, what indicators are used by Insurance companies in pricing the products, analyzing the technique of calculating the Sharia contribution and what things are distinguished in calculating prices. This research is an associative research and case study with qualitative research methods that aims to determine the relationship between two or more variables. Data collection techniques are carried out by conducting literature studies (library research), field studies (field research), while to obtain primary data is done through direct observation to the Sharia Insurance companies, having interviews and discussions with industrial players, chairman of the Sharia Insurance Association and Director of IKNB Sharia Financial Services Authority. The results of the study concluded that there were no technical standards for pricing Sharia contribution, there is no specific Policy that regulated the operational activities of Sharia insurance companies, including the study of minimum capital determination policies in accordance with the characteristics of Sharia Insurance companies. Until now Sharia Insurance still adopts, applies, the same rules and policies as Conventional Insurance. This is supposed to be provided flexibility and aligned with the development of